MEREDUKSI AJARAN SESAT DALAM KOMUNITAS KRISTEN DI ERA DIGITAL: TELAAH TEOLOGIS PERAN GEMBALA SEBAGAI PENJAGA IMAN JEMAAT - Ayub Pangga Lewu (Sekolah Tinggi Teologi Arastamar Bengkulu, 2025)
Heretical teachings pose a serious and growing threat to contemporary Christian communities, particularly in the digital age, which allows for their massive and unrestricted spread across digital platforms. The presence of these deviant teachings not only undermines sound doctrine but also damages the spirituality of congregations that lack a solid foundation of faith. In many churches, this phenomenon is exacerbated by weak theological resilience and a lack of spiritual oversight from church leaders. The phenomenon of pastors focusing more on managing ministry than maintaining doctrine worsens the situation. This study aims to theologically examine the role of pastors as guardians of the faith and spirituality of the congregation in facing heretical teachings. The research method used is descriptive qualitative through a literature review of biblical sources, pastoral theology, and academic literature. The findings of this study conclude that the presence of heretical teachings within Christian communities necessitates an understanding of their characteristics and their impact on the spirituality of the congregation. Therefore, pastors have a theological responsibility from a biblical perspective. Thus, pastoral strategies are needed to reduce heretical teachings: education, training, and church discipline. This is a formulation of pastoral leadership theology in the context of the crisis of truth and contemporary heretical teachings. Therefore, the church needs to equip pastors theologically and pastorally to maintain the integrity of the faith of the congregation.